1974
DOI: 10.1126/science.185.4149.449
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Morphine Tolerance after Medial Thalamic Lesions in the Rat

Abstract: Tolerance, manifested by a diminished electroencephalographic response at cortical and subcortical recording sites, was found in rats subjected to repeated systemic injections of morphine sulfate. Reversal of tolerance to morphine resulted from destruction of the medial thalamus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1976
1976
1988
1988

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…Reported use of morphine results in the development of dependence and tolerance t o the drug. It has been shown that lesions in the limbic structures, hypothalamic nuclei, and MTh can result in a complete or partial loss of tolerance to the opiates [31,32,47,49]. In the present investigation, all the reports concerning the site of morphine action were taken into consideration and electrodes were inserted in structures related to motor coordination, analgesia, temperature regulation, and in central sites where 5HT, NE, and DA are synthesized.…”
Section: Discuss1 Onmentioning
confidence: 99%
“…Reported use of morphine results in the development of dependence and tolerance t o the drug. It has been shown that lesions in the limbic structures, hypothalamic nuclei, and MTh can result in a complete or partial loss of tolerance to the opiates [31,32,47,49]. In the present investigation, all the reports concerning the site of morphine action were taken into consideration and electrodes were inserted in structures related to motor coordination, analgesia, temperature regulation, and in central sites where 5HT, NE, and DA are synthesized.…”
Section: Discuss1 Onmentioning
confidence: 99%
“…Recently some investigators have suggested that the medial thalamus is an important brain site involved in the development of tolerance to the EEG effects of morphine (Teitelbaum, Catravas & McFarland, 1974) and the naloxone-precipitated abstinence syndrome in the rat (Wei, Loh & Way, 1973a and b). It (Shute & Lewis, 1967) which projects diffusely to the cortex and releases ACh in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Since the manifestation of opiate withdrawal is dependent upon the activity of several discrete brain areas [Kerr and Pozuelo, 1971;Teitelbaum et al, 1974;Laschka et al, 19761, these results indicate that rIFN-a has direct neuromodulatory activity. However, in lieu of our previous studies upon systemically administered rIFN-a and withdrawal severity, it is evident that i.c.v.…”
Section: Results Experiments Amentioning
confidence: 99%